Teknologi Artifical Intelligent Dalam Mengembangkan Kecerdasan Emosional - Zulfitria, Zulfitria; Efendi, Yasin; Wathoni, Mahbubul; Nurbojatmiko, Nurbojatimko; Arif, Zainal (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
Artificial Intelligence (AI) technology is a breakthrough in the field of educational technology to facilitate learning. The wise and controlled use of technology can trigger the acceleration of education. The emergence of artificial intelligence technology can also instill an independent nature in students. Teachers are not burdened with such a dominant role, however, their duties are specific in the scope of providing enlightenment with substantial keywords. The basis of every use of technology for teachers is to continue to prioritize the essence of teaching, namely managing the morals and behavior of students. Students developing their emotional intelligence can take advantage of AI technology by sorting out the good things from the uses of AI so that educational technology can help them control and monitor their own learning, enabling them to live and work well in the future.